MON-001 Peripartum Sertraline (Zoloft®) Increases Pup Mortality Immediately Postpartum - Sheftel, Celeste (J Endocr Soc, 2020)
Peripartum and postpartum depression can be detrimental to both the mother and the developing child. Use of antidepressants, such as selective serotonin reuptake inhibitors (SSRIs), is common during the peripartal period and SSRIs have been the leading prescribed antidepressant to treat maternal depression. One of the most commonly prescribed SSRIs is sertraline (Zoloft®) because of the limited fetal teratogenic effects observed, unlike maternal paroxetine (Paxil®) usage which can manifest in fetal cardiovascular defects. Fluoxetine (Prozac®), like sertraline, has previously been shown to have limited teratogenic effects, however, we have shown treatment with fluoxetine for the entire period of pregnancy and lactation in mice compromises pup bones at weaning resulting in decreased long bone length and head circumference. Furthermore, maternal fluoxetine usage results in a sustained reduction in maternal bone mineral density post weaning, which may lead to long-term osteopenia, putting the mother at risk for bone-related disorders later in life. We hypothesized sertraline, like fluoxetine, will compromise maternal bone postpartum and fetal bone development at weaning. Treatment with sertraline in C57BL/6 dams throughout pregnancy and lactation reduced litter size (5.4 pups/dam) and increased pup mortality during the first 24 hours postpartum (20% dead pups/litter) compared to controls (6.8 pups/dam, 5% dead pups/litter, respectively; P < 0.018). Maternal calcium transporters (Orai1 and Serca2) were downregulated in the mammary gland in sertraline-treated dams on day 21 of lactation (P < 0.0032). Together, our data suggests in utero pharmacological exposure to sertraline may induce a failure to thrive in the pups and alters calcium metabolism in the dam. SSRI exposure during pregnancy and lactation may adversely affect the developing neonate(s) as well as have lasting impacts on the mother.